Effect of pine bark extract on bond strength of brackets bonded to bleached human tooth enamel. - Aksakalli, Sertac; Ileri, Zehra; Karacam, Nejla (My University, 2013)
The purpose was to investigate the effect of pine bark (proanthocyanidin, natural antioxidant) solution on the shear bond strength (SBS) of metal brackets bonded with composite resin to human enamel after bleaching with hydrogen peroxide (HP).

Sixty recently extracted premolars were divided into an experimental group (n = 45), which was bleached with 40% HP, and a control group (n = 15), which was not bleached. The experimental group was further divided into three sub-groups. Specimens in group IB (n = 15) were bonded immediately after bleaching; specimens in group SA (n = 15) were bleached, then treated with 10% sodium ascorbate and then bonded; group PB specimens (n = 15) were bleached, then treated with 5% pine bark solution and bonded. The specimens were debonded with Universal testing machine. The adhesive remnant index was calculated.

No significant differences in shear bond strength were noted when the pine bark treated group was compared with the control group and sodium ascorbate group (p > 0.05). Treating the bleached enamel surface with 10% sodium ascorbate or 5% pine bark solution reverses the SBS reduction.

So, as a natural antioxidant and less hazardous, clinicians can choose pine bark solution instead of sodium ascorbate.